Sources, Rates and Time of Nitrogen Application on Maize Crops under No-Tillage System. Issue 19 (27th October 2016) - Souza, J. A.; Buzetti, S.; Teixeira Filho, M. C. M.; Moreira, A.
ABSTRACT: Quantitatively, nitrogen (N) is the foremost nutrient for maize crops ( Zea mays L.), but the N source to increase the grain productivity still needs more investigation. Thus, the aim of this experiment was to study sources, rates and time of N application on the crop yield and agronomic characteristics of the maize under no-tillage system. The experiment was carried out during two growing seasons on an Oxisol under the factorial 5 × 3 × 3 scheme with five N rates (0, 50, 100, 150, and 200 kg ha −1 ) and three sources (ammonium-sulfate-nitrate as inhibitor of the nitrification (ASN+I), ammonium sulfate (AS) and urea); we applied them two times with four replicates: first time at the sowing or later under side dressing when the plants had the six leaves stage. In the first year, the sources of N had no influence on the number of grain line /ear (NGLE), grain number/line (GNL), total number of grain/ear (TNFE), biomass of 100 grain, plant height (PH), height of the first ear insertion (AFEI) and stalk diameter, in contrast with the foliar N content and the crop yield. Early fertilization with N at the sowing time can afford applications as well as the total side dressing. The increase of the rates had positive influence on the N foliar content, plant height and 100 grains biomass. The highest productivities were found with rates above the threshold of 150 kg ha −1, no matter the sources and the fertilization time.